Climate change in Latin America: public policy and legislation for adaptation - Pérez Melchor, Seerlay Yadira (2019)
The objective of this article is to present the progress, difficulties and challenges of public policy in terms of legislation on measures to adapt to climate change in Latin America in the period from 2000 to 2017. From a prospective analysis and of interpretation that included two phases, a review of documentary sources on public policies and existing regulations on climate change was carried out, as well as some implementation experiences that have been documented. This resulted in results, in terms of progress, that most countries in the region have implemented mechanisms and strategies to adapt their territories to climate change, covered by current legislation. While, with respect to the difficulties, some countries lack a regulatory framework that guarantees the implementation of these adaptation plans and programs already prepared. One of the challenges faced by the governments in power is the advancement of environmental governance that articulates the resilience capacities of the populations and the adaptation strategies linked to the development processes in the territory. It should be noted that it is not part of the present study to conduct a sequential analysis of public policy, nor to address mitigation strategies in relation to climate change in parallel, aspects that could constitute an object of study for future research.